Solar Updraft Power Technology: Fighting Global Warming and Rising Energy Costs - Krätzig, Wilfried B. (Journal of Technology Innovations in Renewable Energy, 2015)
Solar updraft power technology (SUPT) forms a highly innovative, modern and efficient concept for solar-based electricity generation. Solar updraft power plants (SUPPs) are fueled purely by solar irradiation. They require no water for power generation, so their ideal locations are deserts. A SUPP consists of the glass-covered collector area (CA), in its centre the solar chimney (SC), and around the SC’s perimeter the power conversion units (PCU). This arrangement causes a permanent flow of warm air through the SUPP, producing electricity. The paper describes computer simulation concepts to evaluate the power/energy harvest in such plants, based on fluid-thermodynamics and radiation-physics. The nonlinear numerical processes for the SUPPs’ power harvests are solved by fast computer algorithms. Finally, the high economy of SUPT for world-wide arid zones in terms of leveled electricity costs (LECs) is exemplified by several optimized SUPPs.